Dynamic causal relationship between Islamic banking and economic growth: Malaysian evidence - Khaliq, Ahmad; Mohd Thas Thaker, Hassanudin (European Research Centre for Islamic Finance, 2017)
Islamic banking and finance have emerged as one component of a significant competitive and comprehensive market, where it is reliable with conventional financial development in term of economic contribution. As of today, Islamic banking accounts for a minimum of 11 percent growth in Malaysia economic development and indirectly contributes to the global agenda of developing sustainable growth. Thus, this paper aims to empirically assess the dynamic contribution of Islamic banking towards economic growth in Malaysia based on selected variables, namely, real gross domestic product (GDP), total deposit, total financing, total assets and non-performing loan. The quarterly time – series data from (2007: Q1 – 2014: Q1) are used to uncover short–run and long–run relationship between real GDP and Islamic banking key financial indicators. Using a battery of time series econometric techniques, we document that there is robust evidence suggesting favourable result where Islamic banking does contribute towards economic growth in the long-run where the total deposit, total financing and total assets of Islamic banking have a positive relationship where the non-performing loan is found to have a negative relationship. To test the causality relationship of variables in the short-run, the Wald – test Granger Causality has been carried out and it shows that there is evidence of a bi-directional causality relationship between economic growth and total deposit of Islamic banks. In addition, the bidirectional relationship also exists between non-performing loan and total deposit of Islamic banks. However, the majority of the variables are found to be having unidirectional causality relationship among the variables. Overall, our conclusion state that Islamic banking and finance still act as one of the dominant key contributors to Malaysian economic development and growth. The results obtained in this paper are much more robust to alternative econometric specifications